Validation and Assessment of a Tool to Measure Psychosocial Readiness to Use Modern Contraceptives among Women in Tigray, Ethiopia. Issue 1 (12th March 2022) - Anderson, Elizabeth J.; Hinson, Laura; Berhe, Hailemariam; Berhane, Kesete; Warholak, Terri; Equar, Awala; Hailu, Desta; Abraha, Atsbaha
Abstract: Social norms, beliefs, and attitudes around modern contraception (MC) use can influence the decision to take up a method, but susceptibility to these factors varies between individuals. The effect of psychosocial readiness to use MC at the individual level is not established for women in Ethiopia. Data from 349 women were used for validity and reliability testing of a 12‐item MC psychosocial readiness scale. A rating‐scale Rasch model tested for unidimensionality, rating scale functioning, and construct and content validity. Multiple linear regression assessed the effect of respondent characteristics on MC psychosocial readiness scores. The psychometric properties of the univariate MC psychosocial readiness scale were satisfactory after the stepwise removal of two items. Prior MC use, socioeconomic status, geographic zone, and education were significantly associated with increased endorsement of MC psychosocial readiness. The 10‐item scale measures the extent of endorsement of MC psychosocial readiness for childbearing women in Tigray, Ethiopia. Further research should qualitatively explore the identified influence of education on MC psychosocial readiness.